2023
DOI: 10.26668/businessreview/2023.v8i4.1286
|View full text |Cite
|
Sign up to set email alerts
|

Customer Loyalty Islamic Banks in Indonesia: Service Quality Which Mediated by Satisfaction and Customer Trust

Abstract: Purpose: This study aims to analyze the effect of service quality on loyalty mediated by customer satisfaction and trust. A total of 215 Islamic bank customers in the study area were sampled accidently.   Theoretical framework: Theoretically, this study contributes to the gaps in the literature, especially those related to the effect of SQ on Islamic banking loyalty which is mediated by satisfaction and trust simultaneously in one research title. Practically, encouraging Islamic banking management to design SQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In the same way, many researchers investigated the procedures defined towards the advancement in mobile banking contributing to customer satisfaction and tried to mark the mediating part of the trust for customer satisfaction. Some researchers have counted mediator dimensions to present a contribution towards customer satisfaction [28], [29], [30], [31]. The author in [32] evaluated the dimensions contributing towards customer satisfaction and evaluated that risk of performance and perceived value are among vital dimensions; as per the study, working towards perceived value marks more Impact on customer satisfaction than trying to reduce the risk for performance.…”
Section: A Literature Depiction Of Individual Behavior Toward Custome...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the same way, many researchers investigated the procedures defined towards the advancement in mobile banking contributing to customer satisfaction and tried to mark the mediating part of the trust for customer satisfaction. Some researchers have counted mediator dimensions to present a contribution towards customer satisfaction [28], [29], [30], [31]. The author in [32] evaluated the dimensions contributing towards customer satisfaction and evaluated that risk of performance and perceived value are among vital dimensions; as per the study, working towards perceived value marks more Impact on customer satisfaction than trying to reduce the risk for performance.…”
Section: A Literature Depiction Of Individual Behavior Toward Custome...mentioning
confidence: 99%
“…Given the various e-banking offerings, quality of service (e.g., concreteness, dependability, and empathy) has a highly significant impact on customer satisfaction. Various authors have demonstrated a positive correlation between the quality of services and customer satisfaction [44], [45], [46]. An expanded analysis of dimensions shows dependability, Efficiency, adaptability, and interactions, as well as security and privacy, as crucial factors influencing customer satisfaction [47], [48], [49].…”
Section: Literature Depiction For Quality Of Services Towards Custome...mentioning
confidence: 99%
See 1 more Smart Citation
“…The long-term maintenance of cooperative relationships requires mutual trust among channel members. The trust between channel members will increase the quality and maintenance of the relationships (Kadir, Paly, & Abdullah, 2023). Trust can also reduce conflict between channel members.…”
Section: Economic Power and Channel Relationship Continuitymentioning
confidence: 99%
“…These studies report that customers place importance on several criteria ranging from religious to non-religious reasons when choosing an Islamic bank. Shamsudheen et al, (2021), clarifies this, and states that customers initially supported Islamic banks because of religion, however as the industry grows, customers are placing emphasis on other aspects such as service quality, the range of products and services and the level of corporate social responsibility (Awan & Bukhari, 2011;Ergec et al, 2016;Kadir et al, 2023;Lajuni et al, 2017). Thus, the truism that Muslims are motivated to support Islamic banks on religious grounds is in question (Iqbal et al, 2018).…”
Section: Introductionmentioning
confidence: 99%